Nucleotide sequence of yst, the Yersinia enterocolitica gene encoding the heat-stable enterotoxin, and prevalence of the gene among pathogenic and nonpathogenic yersiniae. - Delor, I (1990)
The gene encoding the heat-stable enterotoxin (yst) was cloned from the chromosome of Yersinia enterocolitica W1024 (serotype O:9), and the nucleotide sequence was determined. The yst gene encodes a 71-amino-acid polypeptide. The C-terminal 30 amino acids of the predicted protein exactly correspond to the amino acid sequence of the toxin extracted from culture supernatants (T. Takao, N. Tominaga, and Y. Shimonishi, Biochem. Biophys. Res. Commun. 125:845-851, 1984). The N-terminal 18 amino acids have the properties of a signal sequence. The central 22 residues are removed during or after the secretion process. This organization in three domains (Pre, Pro, and mature Yst) resembles that of the enterotoxin STa of Escherichia coli. The degree of conservation between the E. coli and Y. enterocolitica toxins is much lower in the Pre and the Pro domains than in the mature proteins. The mature toxin of Y. enterocolitica is much larger than that of E. coli, but the active domain appears to be highly conserved. The yst gene of Y. enterocolitica introduced in E. coli K-12 directed the secretion of an active toxin. The cloned yst gene was used as an epidemiological probe among a collection of 174 strains representative of all Yersinia species except Yersinia pestis and numerous Y. enterocolitica subgroups. In Y. enterocolitica, there was a clear-cut difference between pathogenic and nonpathogenic strains: 89 of 89 pathogenic and none of 51 nonpathogenic strains contained yst-homologous DNA, suggesting that Yst is involved in pathogenesis. Among the other Yersinia species, only four strains of Yersinia kristensenii had DNA homologous to yst.